2017
DOI: 10.18632/oncotarget.15298
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic roles of alterations in vitamin D and vitamin D receptor in gastric tumorigenesis

Abstract: Gastric cancer is currently the second leading cause of cancer-related death worldwide, especially in Japan, Korea and China, and the 5-year survival rate of gastric cancer is less than 30%. Thus, it is important to shed more lights on novel agents to prevent gastric cancer or to improve survival rate of the patients. Vitamin D not only maintains calcium and bone homeostasis, but also mostly inhibits tumor genesis, invasion, and metastasis through activation of vitamin D receptor. Although epidemiological resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 103 publications
0
28
0
Order By: Relevance
“…Du et al reported that 1α,25(OH) 2 D3 and the VDR interaction can induce a cascade of gene regulation and cell signaling reactions to promote anti-tumor mechanisms [163]. Vitamin D and its analogues play an important role in reducing the risk of gastric adenocarcinomas.…”
Section: Vitamin D and The Gastric Tissuementioning
confidence: 99%
“…Du et al reported that 1α,25(OH) 2 D3 and the VDR interaction can induce a cascade of gene regulation and cell signaling reactions to promote anti-tumor mechanisms [163]. Vitamin D and its analogues play an important role in reducing the risk of gastric adenocarcinomas.…”
Section: Vitamin D and The Gastric Tissuementioning
confidence: 99%
“…However, in Australia, the reduced risk of esophageal cancer with lifetime ambient UV radiation was limited to esophageal and esophagogastric junction adenocarcinomas, with no reduction for esophageal squamous cell carcinoma [72]. A further review in 2017 reported accumulating evidence from gastric cancer cells, animal models, and clinical trials to suggest that vitamin D deficiency may increase the risk and mortality of gastric cancer, implying that vitamin D supplementation might be a safe and economical way to reduce gastric cancer risks both prospectively and during treatment [73]. Supporting evidence that vitamin D has the potential to reduce the risk of gastric cancer is provided by studies reporting that vitamin D repletion can eradicate Helicobacter pylori infection, itself an important risk factor for gastric cancer [74,75].…”
Section: Resultsmentioning
confidence: 99%
“…A recent meta-analysis reported that sufficient vitamin D could be associated with a decrease in H. pylori infection, a major risk factor for GC [ 6 ]. A review study by Du et al suggested that vitamin D may inhibit viability, proliferation and metastasis of gastric cancer cells and inhibit Helicobacter pylori infection and Helicobacter -related gastric cancer [ 7 ]. Conversely, another meta-analysis study reported no statistically significant relationship between serum vitamin D concentrations and risk of GC, for the whole population nor for gender-stratified analyses [ 8 ].…”
Section: Introductionmentioning
confidence: 99%